Comparison of Quality of Life of Diabetes Mellitus Ulcer Patients with Non Ulcer Patients at Kota Agung Hospital - Stiawan, Usman; Sahyana, Sahyana; Putri, Riska Hediya; Hardono, Hardono (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objectives: Diabetes mellitus (DM) is currently one of the global health threats, worldwide nearly half a billion people live with diabetes. Poor quality of life of patients with DM results in decreased self-care, worsening the situation over time. Quality of life issues become an important aspect in diabetes mellitus with ulcers or non-ulcers.Tujian in this study to determine “Comparison of Quality of Life of Patients with DM Ulcers with Non Ulcers at Kota Agung Hospital”. Methods: This research method uses descriptive with a cross sectional approach, this research was conducted at Kota Agung Hospital during December 15 - January 07. The sampling technique used total sampling, which was 20 respondents, of the 20 respondents there were 10 respondents with diabetic ulcers and 10 non-diabetic ulcer respondents as well as the World Health Organization Quality of Life (WHOQoL) questionnaire developed by WHO to assess quality of life, data analysis using the mann withney test. Results: Based on the results of the Mann-Whitney test, the p-value = 0.000 indicates that ha is accepted and ho is rejected, which means that there is a comparison between the quality of life of non-ulcer DM patients and the quality of life of DM patients with ulcers. Conclusion: It is hoped that the management of the Great City Hospital can create an assessment unit for the quality of life of non-ulcer DM patients and diabetic ulcers, in order to improve the quality of life of patients.